Resiliensi MIS Arofa Dalam Menjaga Kualitas Literasi Al-Qur’an di Tengah Defisit Guru Lulusan Keagamaan dan Disparitas Kesejahteraan Pendidik - Muhammad Al Faiz Hikmatyar Nasution; Zulkipli Nasution (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The gold mining industry in Batang Toru causes a stark income disparity, leading to a shortage of religious teachers at MIS Arofa Kampung Telok and challenging the quality of Islamic education. This descriptive qualitative study investigates this teacher deficit, its financial impacts, and the madrasah’s survival strategies. Data collected via observation, interviews, and documentation were analyzed using the Miles and Huberman model. The findings confirm that high profits in the mining sector decrease university graduates' interest in teaching, hindering religious staff recruitment. To adapt, the madrasah optimizes internal capacity by conducting regular tahsin training for existing teachers and involving general subject teachers in Quranic guidance. This study concludes that continuous organizational resilience effectively maintains students' Quranic literacy standards (fluency, makhraj, tajwid, and Juz 29–30 memorization) amidst local economic pressures and teacher shortages.